Application of the HVSR Microtremor Method for Basalt Outcrops in Tanjung Batu, Jambi - H. Nasri MZ; Surya Bakti Rangkuti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
Microtremor data at 15 point had been taken at tanjung batu around of outcrop igneous rock in back arc basin south sumatra such as carried out at sub basin jambi. The igneous rock, which is found in this area, is basalt and distributed in Â± 825 Ha and located in Desa Tanjung Batu Geragai Jambi. The uniqueness of this outcrop is it intrudes the thick of sedimentary rock which have the thickness around more than 1000 meter, located in east cost of Sumatera Island and far away from the volcanoes. The natural frequency from 1-11 and 15 measurement point varied from 6 Hz-19 Hz. The amplification value from 1-10 and 15 measurement point varied from 0,8 Hz-2,2Hz, but at points 4 and 11 have amplification value from 3,4 Hz and 4,8 Hz. Seismic vulnerability at 1-10 and 15 measurement point varied from 0,8-1,8. but at points 4 and 11 have seismic vulnerability value from 1,4 and 2,3. From these result of natural frequency, amplification, and Seismic vulnerability in the outcrops have contrasting value in each map can be identified as fault from intrusion of basalt.